EFL Pre-Service Teacher’s Perception During Kampus Mengajar: A Case Study - Irwan Sulistyanto; Kurniawan, Erwin Hari; Prayoga, Krisna Adi (Universitas Pendidikan Ganesha, 2024)
Classroom management skills of prospective English as a second language (EFL) teachers are inseparable. Professionalism requires a balance between theoretical education in the classroom and real-world experience. This article aims to analyze the perceptions of pre-service EFL teachers during the Kampus Mengajar program. Three alumni of the 7th batch of pre-service EFL teachers who teach in Junior High Schools were purposively selected as the subjects of this study. This study used a descriptive qualitative design. To collect data, semi-structured interviews were used. The data analysis of this study used the interactive model of Miles and Huberman. The results of the study showed that pre-service EFL teachers had positive perceptions during the Kampus Mengajar program. However, there were also many challenges faced by the participants during Kampus Mengajar, namely (1) Difficulty in instructional materials, (2) student motivation, (3) technology integration, and (4) busy teacher schedules. In addition, there were also several strategies used by the participants to overcome these obstacles, such as maximizing preparation before teaching, using appropriate teaching strategies and technology integration, and having good teaching aids. Despite all that, the Kampus Mengajar program is recommended to be implemented as one way to improve faculty accreditation scores, an evaluation tool for the Independent Curriculum and an authentic experience for pre-service EFL teachers in the reality of school life.